Digital Authentic Resource and Activity Needs of English Major Students for Autonomous Learning through Self-Access Center (SAC) - Slamet Asari; Nirwanto Ma’ruf; Mukamil Mukamil (Edulitics (Education, Literature, and Linguistics) Journal, 2023)
To boost English major students’ autonomous learning beyond classroom learning through the Self-Access Center (SAC), the provision of learning resources and activities in SAC should meet their needs. The issue that arises is that little is known about the specific needs of autonomous learning in SAC for English major students. This research focuses on autonomous learning based on the needs of digital authentic resources and activities through SAC as accelerated learning outside the classroom for students majoring in English. A mixed method was applied based on the need analysis model by Hutchinson and Waters (1987). Around 51 English major students of UMM as users of “American Corner” (Amcor) UMM were required to fill out the questionnaires consisting of 6 questions adapted from Ortiz (2006) and 16 of them were selected as interview participants. Observation was also held to support both data. The findings revealed the digital authentic resource needed, lacking, and wanted the most by English major students. Additionally, the types of activities needed the most to support autonomous learning in SAC were also described. The implication of the research is for SAC managers to consider future development and recommendations of resource provision as well as ideas for forthcoming programs of SAC based on the identified needs particularly for the English major students.